PENGEMBANGAN MEDIA E-LEARNING PADA MATA KULIAH KOMPUTASI I DI PERGURUAN TINGGI. - Achmad Buchori (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2012)
Media Development E-Learning in Computing I course at the university.This study aims to acquire e-learning instructional media are valid for self-study student in the course of computing I. Population in the study were all students of third semester of mathematics education IKIP PGRI Semarang. This study is a research and development. In media studies e-learning development is carried out with 4 (four) stages, namely (a) a preliminary analysis, (b) Design, (c) Evaluation, (d) Revised. Processing the data using descriptive qualitative data analysis techniques. Corresponding results of questionnaires about the development of e-learning in the obtained value sig = 0.00 and R = 0,541, which means it affects the motivation for 54.1% of the student learning outcomes. Gained an average of better learning outcomes between the experimental class at 84.27 compared with 80.05 for the control class. The results obtained from the e-learning instructional media are valid for independent study students on computing courses I according to developmental theory Akker and student learning outcomes.